Withanolides: Biologically Active Constituents in the Treatment of Alzheimer’s Disease - A. Khan, Shahid; B. Khan, Sher; Shah, Zarbad; M. Asiri, Abdullah (Medicinal Chemistry, 2016)
The use of natural products in drug discovery and development have an important history. Several therapeutic agents have been investigated during the biological screenings of natural compounds. It is well documented that plants are possibly the core of novel substances that led to the discovery of new, novel, and effective therapeutic agents. Therefore, in the last few decades, scientists were thoroughly attempting for the search of benevolent drugs to protect mankind from various diseases and discomforts. The diverse chemical structures of natural products are the key element of their success in modern drug discovery. Cholinesterase enzyme inhibitors (ChEI) are chemicals which inhibit the splitting of cholinesterase enzymes (acetylcholinesterase and butyrylcholinesterase). Acetyl cholinesterase (AChE) and butyrylcholinesterase (BChE) are two types of cholinesterase enzymes that have been identified in vertebrates that are responsible for Alzheimer’s disease and related dementia. Withanolides are affective plant secondary metabolites which inhibit acetylcholinesterase and butyrylcholinesterase enzyme and thus possibly will be the future drug for Alzheimer’s disease. By viewing the importance of natural products in drug discovery and development, we present here, the importance of withanolides in the treatment of Alzheimer’s disease. In this article, we also describe the classification and structural characterization of withanolides. This review comprises of 114 compounds.
Keywords: alzheimer’s disease